2015
DOI: 10.3109/13880209.2015.1079725
|View full text |Cite
|
Sign up to set email alerts
|

Thai red rice extract provides liver protection in paracetamol-treated mice by restoring the glutathione system

Abstract: Context: The incidence of drug-induced liver disease associated with oxidant-antioxidant imbalance is increasing. Colored rice can potentially improve these hepatic disorders through antioxidative and glutathione-restoring effects. , O 2 , metal chelating, and lipid peroxidation, respectively). Mice administered paracetamol exhibited increases in GPT/GOT with decreases in GSH and GSH/GSSG ratio followed by histomorphological signs of liver injury. In the presence of the Hom-Dang extract, the GPT/GOT values wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…1d). The previous report also showed that Hom Dang rice bran extract can scavenge the superoxide anion and hydroxyl radicals due to its bioactive compounds contents 45 . These results well corroborate a previous finding that quercetin significantly suppresses the level of malondialdehyde, a naturally end product of lipid peroxidation and an oxidative stress biomarker, which could contribute to the protective effect on cell membranes 42 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1d). The previous report also showed that Hom Dang rice bran extract can scavenge the superoxide anion and hydroxyl radicals due to its bioactive compounds contents 45 . These results well corroborate a previous finding that quercetin significantly suppresses the level of malondialdehyde, a naturally end product of lipid peroxidation and an oxidative stress biomarker, which could contribute to the protective effect on cell membranes 42 .…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, catechin present in the red rice bran (Table 2) also acts as a powerful hydrogen-donating radical scavenger of ROS and RNS and chelates divalent transition metal ions (Cu 2+ , Zn 2+ and Fe 2+ ), thereby preventing the Fe 2+ -induced formation of free radicals 58 . It also increases the expression of manganese superoxide dismutase SOD2 gene in Drosophila melanogaster and inhibits the signaling of transcription factor NF- κ B, leading to reductions in liver and kidney damage, and improvement of age-associated inflammation and oxidative stress in mice 45 . Thus, the evidence provided here and in other studies clearly support the antioxidative-assisted anti-aging effects of the pigmented rice extract and antioxidant compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction was stopped by adding 4 N NaOH before measuring the absorbance at a wavelength of 505 nm. The ALT and AST levels were determined using pyruvate as a standard [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…for 30 days ICR mice, 60 mg/kg p.o. for 30 days ↑GSH; ↓GSSH [109] Methanol extract of Adansonia digitata L. (Malvaceae) 200 mg/kg p.o. for 7 days Wistar rats,2 g/kg p.o.…”
Section: Targeting Mitochondrial Oxidative Stress and Dysfunction Formentioning
confidence: 99%